The golden throne : Hephaestus, Ares - Στεφανίδης, Μενέλαος Δημ. (Greek mythology : The gods of Olympus, 1992)
Hephaestus tames fire. A "gift" for Hera. The arms of Achilles. Fire and Water. Ares the bloodthirsty. A painful lesson. Heracles and Cycnus. Ares in Hephaestus' trap.